Effect of the A30P mutation on the structural dynamics of micelle-bound alpha synuclein released in water: a molecular dynamics study - Chatterjee, Prathit; Sengupta, Neelanjana (European Biophysics Journal With Biophysics Letters, 2012)
Atomistic molecular dynamics simulation has been used to probe the effect of the A30P mutation on the structural dynamics of micelle-bound, helical alpha Synuclein when released in an aqueous environment. On the timescales simulated, the effect of the mutation on the secondary structure is restricted to local changes close to the mutation site in the N-terminal helical domain. The changes are transient, and all residues except Lys23 recover their initial structure. The local behavior due to the mutation gives rise to a global difference in the A30P mutant in the form of a permanent kink in the N-terminal helical domain.
Keywords: A30P mutation; Alpha synuclein; Kink formation; molecular dynamics simulation; Structural persistence